Recent Trends in Pharmaceutical Analytical Chemistry - Zacharis, Constantinos K.; Markopoulou, Aikaterini (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book covers the most recent research trends and applications of Pharmaceutical Analytical Chemistry. The included topics range from the adulteration of dietary supplements, to the determination of drugs in biological samples with the aim to investigate their pharmacokinetic properties.